T Cell Differentiation and Function in Tissue Inflammation - Awasthi, Amit; Goswami, Ritobrata (Frontiers Media SA, 2020)
Helper T cells play a critical role in the induction of tissue inflammation in immunity and autoimmunity. Various subsets of T cells such as Th1, Th2, Th9 and Th17 cells have been shown to play a key role in the induction of tissue inflammation in allergic and organ-specific autoimmune inflammation. On the other hand, regulatory cells such as Foxp3+Tregs and Tr1 cells are essential to control functions of effector T cells and maintain tissue homeostasis. Distinct transcriptional and molecular pathways have been identified for the generation of various effector and regulatory T cells. Emerging molecular signatures of these effectors and of regulatory T cells indicate plasticity in their developmental pathways, which is dictated by the tissue microenvironment and by other factors including cytokines and transcription factors.